Low temperature hydrothermal synthesis of bismuth sodium titanate nanopowders - Pookmanee P. (2014)
Nanopowders bismuth sodium titanate (Bi0.5Na 0.5TiO3, BNT) were synthesized by the hydrothermal route at low temperature in the range of 150-200°C with different holding periods of 5-20 h. Bismuth nitrate, sodium nitrate and titanium (IV) isopropoxide were used as the starting materials. The phase structure was examined using X-ray diffraction (XRD). The morphology of the formed nanopowders was investigated by scanning electron microscopy (SEM). Rhombohedral BNT nanopowders was obtained without calcination step. The spherical nanopowders were agglomerated. The average sizes of particle size were about 50-200 nm. © World Scientific Publishing Company.